2016
DOI: 10.3168/jds.2015-10012
|View full text |Cite
|
Sign up to set email alerts
|

Heritability estimates for enteric methane emissions from Holstein cattle measured using noninvasive methods

Abstract: The objective of this study was to estimate heritability of enteric methane emissions from dairy cattle. Methane (CH4) and CO2 were measured with a portable air-sampler and analyzer unit based on Fourier transform infrared detection. Data were collected on 3,121 Holstein dairy cows from 20 herds using automatic milking systems. Three CH4 phenotypes were acquired: the ratio between CH4 and CO2 in the breath of the cows (CH4_RATIO), the estimated quantified amount of CH4 (in g/d) measured over a week (CH4_GRAMSw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
122
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 33 publications
19
122
7
1
Order By: Relevance
“…The very negligible positive genetic correlation of PME with production traits suggested that these traits are not able to predict CH 4 emissions alone in dairy cows on a genetic level. Similarly, positive genetic correlations observed between PME and fat and protein corrected MY (0.07 AE 0.09) (Lassen and Løvendahl 2016) was similar to this study (0.06 with MY). There is ongoing debate on those figures because they appear low, but one should not forget that even if PME is also driven by intake it is also strongly related to energy lost or energy efficiency, a different mechanism a priori not (strongly) linked to intake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The very negligible positive genetic correlation of PME with production traits suggested that these traits are not able to predict CH 4 emissions alone in dairy cows on a genetic level. Similarly, positive genetic correlations observed between PME and fat and protein corrected MY (0.07 AE 0.09) (Lassen and Løvendahl 2016) was similar to this study (0.06 with MY). There is ongoing debate on those figures because they appear low, but one should not forget that even if PME is also driven by intake it is also strongly related to energy lost or energy efficiency, a different mechanism a priori not (strongly) linked to intake.…”
Section: Discussionsupporting
confidence: 90%
“…To select any new trait, it must have genetic variation and show heritability. Even with currently only limited research available, CH 4 traits predicted from milk fatty acids (Kandel et al 2015) and measured through non-invasive method (Lassen and Løvendahl 2016) have shown sufficient heritability. Previous studies have shown that mid-infrared (MIR) spectroscopy can be used to predict milk fatty acids (Soyeurt et al 2011) and that milk fatty acids are indirectly related to CH 4 emission (Chilliard et al 2009;Dijkstra et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CH 4 emissions by ruminants have a genetic component, with heritability in the range of 0. 20 to 0.30 (e.g., de Haas et al, 2011;Donoghue et al, 2013;Pinares-Patiño et al, 2013;Kandel et al, 2014;Lassen and Løvendahl, 2016). Breeding for reduced CH 4 emissions, alone or together with other mitigation strategies, could therefore be effective in reducing the environmental impact of cattle farming and, possibly, also in increasing feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated techniques for obtaining measurements of CH 4 emissions from individual cattle in their normal environment using repeated spot measurements [9,[11][12][13]15,18]. The positive correlation between spot measurements of CH 4 obtained during milking and total daily CH 4 emissions by the same cows when housed subsequently in respiration chambers in a previous study [10], and the ability of the technique to detect the effect of diet [10,24], has led to considerable research into the spot measurement technique.…”
Section: Resultsmentioning
confidence: 99%
“…However, as with chambers, the SF 6 technique is not suited to sampling a large population of animals on commercial farms due to restrictions on use of gas and the attachment of equipment to animals. Recent research has focused on collecting data from commercial herds through non-invasive approaches that take repeated spot measurements whilst cattle are feeding [6,9], being milked [10][11][12], or standing [13]. Frequent sampling of gas emissions has been found to provide repeatable measurements that allow assessment of within-cow, between-cow, diet and temporal effects on CH 4 emissions.…”
Section: Introductionmentioning
confidence: 99%